Effects of Tire Pressures and Test Temperatures on Permanent Deformation of Direct Coal Liquefaction Residue Mixture - Zhi, Suo; Jie, Ji; Ran, Zhang; Zhe, Wang; Hui, Yao; Dongzhao, Jin (Frontiers in Materials, 2020)
The main objective of this research is to investigate the permanent deformation of asphalt mixtures containing direct coal liquefaction residue (DCLR) under various tire pressures and temperatures. Three types of asphalt mixtures, including control/DCLR/composite-DCLR modified asphalt mixture, were prepared by the Marshall design method. The rutting test was conducted under a tire pressure range of 0.7–1.0 MPa with a 0.1-MPa interval and at a temperature range of 55–70°C with a 5°C interval. Moreover, the dynamic stability and rutting depth of three asphalt mixtures were obtained to evaluate their resistance of permanent deformation. It was found that the rutting resistance of three asphalt mixtures declines with the increased tire pressures and temperatures. The asphalt mixture containing DCLR has a higher dynamic stability and lower rutting depth compared to the control asphalt mixture under the same conditions. Furthermore, the rutting resistance of composite-DCLR modified asphalt mixture is better than that of DCLR modified asphalt mixture. It indicates that the composite-DCLR is favorable for the improvement of rutting resistance of asphalt mixture. Moreover, the analysis of variance was applied, which analysis results showed that the rutting resistance of asphalt mixture is more sensitive to temperature than tire pressure. Based on the least-squares procedure, the relationship between dynamic stability and rutting depth was obtained, and the accuracy of the prediction is acceptable.